STUDY OF THE USE OF STEM-BASED LEARNING MEDIA - Herlisa Mutiara; Fathur Rokhman; Nuni Widiarti; Agus Yuwono (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to examine the use of STEM-based learning media in various educational perspectives. This literature review analyzes several previous studies that have addressed the effectiveness and implementation of the use of STEM-based learning media on 21st century learning outcomes and skills. This article is a literature review using content analysis techniques using the Systematics Literature Review with Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) approach. The journal criteria used in this study are related to learning media and STEM. The PRISMA approach is carried out through several stages, ranging from identification, screening, and publication selection. The results of the study show that the application of STEM-based learning media is very important in improving scientific literacy, mathematical literacy, improving learning outcomes, and can facilitate early childhood scientific skills. The results of this research are expected to provide in-depth insights for educators, curriculum developers, or researchers in designing or implementing innovative STEM-based learning media and improving the abilities of 21st century students. Keywords: Learning media, STEM